ACTIVITY OF LIPOXYGENASE ON HYPERTRIACYLGLYCEROLAEMIC RATS - Djibril, Naguibou M (My University, 2017)
Lipoxygenases (LOX) are a family of (non-heme), iron-containing enzymes most of which catalyze the dioxygenation of polyunsaturated fatty acids in lipids. The lipoxygenase pathways play a role in leukocyte recruitment through the generation of two classes of arachidonic acid lipid mediators, the leukotrienes and the lipoxins, and one class of omega-3 fatty acid metabolites, the resolvins. There is evidence from animal studies and human genetic studies that the leukotrienes and the enzymes necessary for their generation play a role in atherosclerosis, and possibly even in the development of the vulnerable plaque. The aim of our study was focused on a connection between the activities of: LOX and primary hypertriacyl-glycerolaemia of untreated or treated rats with fenofibrate (2-(4-(4-Chlorobenzoyl)phenoxy)-2-methylpropanoic acid 1-methylethyl ester) an hypolipemiant of the group of statins from Cipla Lmd USA. Our results show that: LOX activity in the cytoplasm derived from the liver of hypertriacyl-glycerolaemic rats is significantly increased (pH 7.2; relative to the control group), which may be one reason for more rapid atherosclerosis progression in lipid metabolism disorders. The highest: LOX activity in microsomes was observed in groups of rats treated with fenofibrate. It appears that fibrates indirectly promote association of LOXs to membranes. In fat fraction, no significant effect of hypertriacyl-glycerolaemia on the activity of: LOX was found. Using gel electrophoresis, significantly different spectrum of proteins was discovered in the control samples and samples of hypertriacyl-glycerolaemic rats. It appears that in condition of lipid metabolism imbalance formation of proteins with low molecular weight (and possibly also the expression of LOX) is elevated.
Keywords: Lipoxygenase; hyper-triacylglycerolaemia; Fatty acids; hypolipemiant